Burden and temporal trends of female-specific cancers in China: A systematic analysis of the 2023 global burden of disease study - Shaoxing Chen; Xiaohuang Yang; Shaona Jiang; Yina Lin; Leijuan Huang; Huiqin Chen; Jinzhu Zheng; Yuanfu Xie; Zhixing Kuang (PLoS ONE, 2026)
Background Female-specific cancers represent a substantial public health challenge in China. This study was designed to evaluate temporal trends and generate future projections of the burden associated with female-specific cancers in China from 1990 to 2023. Methods Data on incidence, mortality, and disability-adjusted life-years (DALYs) attributable to breast, cervical, uterine, and ovarian cancers among women in China were extracted from the Global Burden of Disease (GBD) 2023 database. Joinpoint analysis was used to assess temporal trends, whereas decomposition analysis was applied to quantify the contributions of epidemiological changes, population growth, and ageing to changes in disease burden; a Bayesian age-period-cohort (BAPC) model was further used to project trends in disease burden over the next 15 years. Results Between 1990 and 2023, all age-standardized rates (ASRs) of female-specific cancers in China declined except for the age-standardized incidence rate (ASIR) of breast cancer, which increased from 24.54 (95% uncertainty interval [UI]: 19.7–30.79) per 100,000 in 1990 to 31.62 (95% UI: 25.4–38.22) per 100,000 in 2023. The absolute disease burden increased, with 342,725 (95% UI: 270,872–413,171) new breast cancer cases in 2023, representing a 187.24% increase. In contrast, the numbers of new cases of cervical, uterine, and ovarian cancers were 124,686 (95% UI: 77,638–165,722), 74,990 (95% UI: 53,630–119,885), and 38,969 (95% UI: 31,914–46,805), respectively, with corresponding increases of 43.63%, 82.97%, and 61.76%. Population aging and growth were the main contributing factors, and the BAPC model projected that the absolute disease burden of all four female-specific cancers would continue to increase in the future. Conclusion The burden of female-specific cancers in China remains substantial, underscoring the urgent need to develop targeted prevention and intervention strategies to mitigate this burden.